Urethral prolapse in a 4-year-old girl: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Urethral prolapse is a rare cause of vaginal bleeding in prepubertal females and occursmore commonly in black girls. It is characterized by protrusion of the distal urethral mucosa at orbeyond the level of the urethral meatus. It is often mistaken for sexual abuse in children because itpresents with vaginal bleeding, creating anxiety among parents and confusion among clinicians.Case presentation: A 4-year-old girl presented to the outpatient department with a 2-day history ofvaginal bleeding. However, no lower abdominal pain was reported. Sexual abuse was initiallysuspected. A diagnosis of urethral prolapse was made during examination under anesthesia.Surgical excision and postoperative care were performed.Conclusion: Urethral prolapse, although rare, can occur in prepubertal black girls and is managedeither surgically or through conservative approaches.